Sikap dan Penerimaan Sosial Siswa Reguler terhadap Siswa Berkebutuhan Khusus: Sebuah Studi di Sekolah Inklusi - Eka Kresnawati; Wiwik Dwi Hastuti; Ahsan Romadlon Junaidi; Ranti Novianti (Universitas Negeri Malang, 2025)
This study aims to examine the acceptance and attitudes of regular students towards the social acceptance of students with special needs in inclusive schools. Inclusive education is expected to create an environment that supports all students, including students with disabilities, to interact and learn together. However, there are challenges in the social acceptance of students with disabilities by regular students, which is often influenced by their own understanding, attitudes and adaptive behaviors. This study used a quantitative approach with a survey design, involving questionnaires, observation and documentation as data collection techniques. Respondents were regular students, students with disabilities and teachers who manage inclusive classes. Data were analyzed using descriptive and inferential statistics. The results showed that while the majority of regular students were empathic, 10% showed a lack of empathy and their social engagement with children with disabilities was limited. Regular students' understanding of disability tended to be low, with about 30% of students having limited understanding. Teachers had positive attitudes towards inclusion but faced challenges in providing sufficient support. Students with disabilities, especially those with autism spectrum disorder (ASD) and intellectual disabilities, struggle with social interactions. In conclusion, although there has been progress in social acceptance, further efforts are needed to improve disability understanding and support to create a more effective inclusive environment.